Arresting Early Childhood Caries with Silver Diamine Fluoride Gel Among Preschool Children: Protocol for a Randomised Clinical Trial - Anthony Yihong Cheng; Jieyi Chen; Faith Miaomiao Zheng; Duangporn Duangthip; Chun Hung Chu (Dentistry Journal)
Background: The World Health Organisation (WHO) included silver diamine fluoride (SDF) in the WHO Model List of Essential Medicines for the management of early childhood caries. SDF is typically available as a 38% aqueous solution, which is watery to apply. A 38% SDF gel has recently been developed, but its caries-arrest effectiveness remains unsubstantiated. The objective of this study is to determine whether the efficacy of a 38% SDF gel is non-inferior to a 38% SDF solution in arresting early childhood caries. Methods: This is a 30-month, randomised, active-controlled, parallel-group non-inferiority pragmatic clinical trial with two arms. The hypothesis is that the 38% SDF gel is not worse than the 38% SDF solution by a non-inferiority margin of 10% caries-arrest rate when applied semi-annually to preschool children. This trial will recruit 630 3-year-old kindergarten children through block randomisation to receive either an application of SDF gel or SDF solution on cavitated carious lesions in their primary teeth every 6 months. The primary outcome is the proportion of soft (active) carious tooth surfaces that turn hard (arrested) at the 30-month follow-up. The same calibrated dentist will conduct 6-monthly dental examinations in the kindergartens to assess the status of carious lesions over 30 months. The examiner, the children, and parents will be blinded to treatments. The parents will be surveyed on their child’s oral health-related behaviours and socioeconomic background to allow adjustment for effect modification. Results: If the anticipated results are obtained, clinicians can use the 38% SDF gel as an alternative of the 38% SDF solution in arresting early childhood caries. Conclusions: As SDF gel is cost-effective, non-invasive, and non-aerosol-generating, it can be widely recommended for caries control. Trial registration: ClinicalTrials.gov NCT06241261. Registered on 7 February 2024.